Evaluation of methodologies for the analysis of toxic degradation products of dithiocarbamates fungicides (2013)
Four methodologies were evaluated for the determination of ethylenethiourea and propylenethiourea in fruits and vegetables. An extraction method using a mixture of methanol:water 3:1 and subsequent clean up with liquid-liquid partition supported on extrelut was selected and optimized. Identification and quantification was carried out using high-efficiency liquid chromatography with diode array detection. The validated methodology is specific and selective, with recoveries between 77,82% and 83,57% with coefficients of variation below 20% and detection limits between 0,003 and 0,006 mg.kg-1. Linearity parameters showed adequate results in the concentration range. The method is robust for the evaluated factors and matrix effect was not observed to any analyte in the whole concentration range tested. It was found traces of ethylenethiourea in one sample of tomato and propylenethiourea in one sample of potato.